ANALISIS RESEPSI KONSUMEN TERHADAP STRATEGI REBRANDING LE MINERALE DALAM MENGHADAPI DUGAAN PRAKTIK GREENWASHING - Nayla Syakira Putri Nayla Syakira Putri; Nurist Surayya Ulfa (Interaksi Online, 2026)
The increasing adoption of healthy lifestyles and rising public concern for environmental sustainability have encouraged many companies to apply green marketing strategies. Nevertheless, not all companies are able to maintain environmental commitments consistently, which has led some of them to be accused of greenwashing. This study examines consumers’ interpretations of Le Minerale’s rebranding strategy in response to greenwashing allegations following the launch of its single-use gallon product. Using a descriptive qualitative approach and Stuart Hall’s reception analysis, data were collected through in-depth interviews with six active consumers. The analysis focuses on six dimensions of rebranding: product associations, environmental engagement, healthy lifestyle associations, public figure endorsements, communication of health and purity values, and social media activities. The findings show that consumer reception is influenced by socio-cultural, individual, and situational factors. Most informants occupied dominant-negotiated and negotiated-oppositional positions. The study concludes that Le Minerale’s rebranding has not fully restored consumer trust in its environmental commitment, indicating the need for greater consistency, transparency, and real sustainability practices.